Strictly speaking, x^2 + 2x + 4 doesn't have solutions; if you want solutions, you must equate <span>x^2 + 2x + 4 to zero:
</span>x^2 + 2x + 4= 0. "Completing the square" seems to be the easiest way to go here:
rewrite x^2 + 2x + 4 as x^2 + 2x + 1^2 - 1^2 = -4, or
(x+1)^2 = -3
or x+1 =i*(plus or minus sqrt(3))
or x = -1 plus or minus i*sqrt(3)
This problem, like any other quadratic equation, has two roots. Note that the fourth possible answer constitutes one part of the two part solution found above.
Answer:
Gimme some time
Step-by-step explanation:
The answer would be s=-60
Well, solve for x.
Combine like terms by performing the opposite operation of subtracting 4x on both sides of the equation
The 4x's will cross out on the right
4x - 4x = 0x = 0
On the left:
2x - 4x = -2x
Now the equation looks like:
-2x + 3 = 2
Continue to combine like terms by subtracting 3 on both sides of the equation
On the left:
3 - 3 = 0
On the right:
2 - 3 = -1
Equation:
-2x = -1
Isolate x by performing the opposite operation of dividing -2 on both sides of the equation
On the left:
-2x ÷ -2 = 1
On the right:
-1 ÷ -2 = 1/2
x= 1/2
So, there is only one solution: 1/2
3x^2 - 7x + 12 = 0 ....subtract 12 from both sides
3x^2 - 7x = -12 ....divide both sides by 3 to get x^2 by itself
x^2 - 7/3x = -4
His work is not accurate because he divided the second term by 4 instead of 3.